BESEK PAPRING : ANTARA MATA PENCAHARIAN, PRESERVASI BUDAYA, DAN PEMBELAJARAN MATEMATIKA: Besek Papring: Local Wisdom as An Alternative Media for Mathematic Learning (Jurnal TEKNODIK, 2022)
Besek is part of the local wisdom of the Papring, Kalipuro, Banyuwangi. Besek making besides being a source of livelihood for Papring residents, especially women, is also a skill that is passed down from generation to generation. Besek is made of woven bamboo with a certain pattern which in the end is a three-dimensional product. This condition shows the existence of mathematical concepts in the process of making besek Papring. Exploration of the making of besek papring shows the process of splitting bamboo, ndawat, drying, working (ngenam, mbucon, ngelimpeni, natasi), and the final process (ngelolop). The mathematical concepts that can be identified from besek Papring include permutations, counting, social arithmetic, sets, arithmetic operations, fractions, time, number patterns, non-standard unit, sequences, 2-dimensional, 3-dimensional, relationships between lines, transformations, and comparisons. The use of besek as a contextual tool in learning mathematics is one of the efforts to make learning more meaningful. Â
Keywords: Besek Papring; Culture; Livelihood; Ethnomathematics; Mathematics Learning